Penerapan Media Ular Tangga Untuk Mengembangkan Aspek Kesadaran Diri Pada Anak Usia Dini - Lestari, Amanda; mutiara; Halifah, Syarifah (IAIN Parepare, 2024)
This research aims to stimulate children's self-awareness through the educational game snakes and ladders in group B of Anugrah Kindergarten, Parepare City, where the results of the researchers in initial observations saw that there were several children who were not able to show self-confidence and understand the rules of the game. This research uses qualitative research with a descriptive approach. Data collection techniques use observation, interviews and documentation. The assessment instrument uses Child Development Achievement Level Standards (STPPA). ). The results of the research show that even when researchers have not implemented educational game tools, there are still many children who have not yet developed. However, after researchers implemented educational game tools, there was progress, although not yet significant. From the results of the researchers' activities, it can be concluded that the development of self-awareness through the game of snakes and ladders where each indicator with its assessment increases.